Perceived Organizational Democracy and Associated Factors: A Focused Systematic Review Based on Studies in Turkey - Geçkil, Tahsin (Frontiers in Psychology, 2022)
This review study provides an opportunity to look at the level of organizational democracy (OD) that a large sample of private- and public-sector employees in an emerging market (Turkey) perceive. The focused systematic review includes empirical studies examining employees' level of OD and associated work and organizational psychological variables, using the Organizational Democracy Scale (ODS) in Turkey. This paper includes studies published between January 2014 and April 2021 in the Google Academic, Dergipark, and Ulakbim databases and on the Turkish National Thesis Center website. From a total of 1,778 records, 37 empirical studies meeting the inclusion criteria were included (with a total of N = 10,370 employees). Of these studies, 67.6% are published articles and manuscripts, 24% are unpublished dissertations, and 43.2% of the studies took place in the public sector. The results suggest that the level of employees' perceived OD was slightly above the medium level (mean: 3.30 ± 81), and the scores of the private-sector employees are higher than those of the public employees. Further, empirical associations between OD and 21 different outcome variables are reported and discussed. To varying extents, significant positive correlations were found between the level of employees' perceived OD and positive organizational variables, such as organizational citizenship behavior, organizational commitment, psychological capital, and job satisfaction. On the other hand, negative significant relationships occurred between OD and negatively evaluated organizational variables, such as job stress and organizational depression. The results of this study support the importance of organizational democracy as a management approach.